Anxiety and depression among university students during the COVID-19 pandemic: a cross-sectional study / Wan Nur Amirah Ibrahim and Norfarahin Alexcius - Ibrahim, Wan Nur Amirah; Alexcius, Norfarahin (Universiti Teknologi MARA, 2023)
Mental health issues have become a growing public health concern around the world, particularly during the COVID-19 pandemic and the MCO. Therefore, this study aims to determine the level of anxiety and depression as well as to compare the anxiety and depression scores among the final-year undergraduate Health Sciences and Accountancy students at the UiTM during the MCO. Final-year students from the faculties of health sciences and accountancy have been given a set of study questions. Students were instructed to complete all questions using the Google Form. Out of 177 students who participated in the study, 52 (48.6%) Health Sciences students suffered from anxiety, and 25 (23.3%) suffered from depression. Meanwhile, 29 (41.4%) of accountancy students were anxious, and 15 (21.4%) were depressed. At UiTM Puncak Alam, Selangor, more than one third of the Accountancy and Health Sciences students were vulnerable to anxiety and sadness during the MCO. The findings also revealed that the mean anxiety score is significantly different between twocourse groups (Health Sciences and Accountancy) students, t(170.78)=2.021, (p=0.02). This study provides authorities with information about university students’ mental health, particularly during the MCO, in order to facilitate further research and useful information.